2015
DOI: 10.1007/s13197-015-2087-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the effect of three commercial enzymes for enzymatic hydrolysis of two substrates (rice bran protein concentrate and soy-been protein) with SDS-PAGE

Abstract: In this research enzymatic hydrolysis of rice bran protein concentrate (RBPC) and soybean Protein (SBP) as control were studied with 3 commercial enzymes (Alcalase®, Papain and acommercial 3-enzyme cocktail containing of 1.6 mg ml − 1 Trypsin, 3.1 mg mlChymotrypsin, 1.3 mg ml −1 Aminopeptidase (SIGMA P7500) and 7.95 mg ml −1 pronase type XIV (SIGMA P5147) by the pH stat method. The hydrolysis was carried out at temperature of 28 C, 60 min and pH 8.00. Results were showed that RBPC, and SBP had higher Degree h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 19 publications
(16 reference statements)
5
30
0
Order By: Relevance
“…Comparing results, it appears that the reactions monitored via NMR reach equilibrium more quickly than those in the literature monitored by other methods. In particular, while both the NMR measurements here and measurements in the literature (Pagan et al 2015;Ahmadifard et al 2016) showed a similar rapid increase at the beginning of hydrolysis, the results from the NMR plateaued sooner than results measured by other methods.…”
Section: Reaction Monitoring and Rate Calculationsupporting
confidence: 79%
See 1 more Smart Citation
“…Comparing results, it appears that the reactions monitored via NMR reach equilibrium more quickly than those in the literature monitored by other methods. In particular, while both the NMR measurements here and measurements in the literature (Pagan et al 2015;Ahmadifard et al 2016) showed a similar rapid increase at the beginning of hydrolysis, the results from the NMR plateaued sooner than results measured by other methods.…”
Section: Reaction Monitoring and Rate Calculationsupporting
confidence: 79%
“…The calculated reaction rates approximate rates found in the literature for hydrolysis using Alcalase and Flavourzyme enzymes under similar experimental conditions (Ahmadifard 2016;Sundekilde et al 2018; Kristoffersen et al 2019). It was observed that the combined Alcalase and Flavourzyme measurement on the red cod produced a slower reaction and a less efficient hydrolyzation than for the Alcalase alone.…”
Section: Reaction Monitoring and Rate Calculationsupporting
confidence: 75%
“…On the other hand, due to the very broad substrate specificity, alcalase can hydrolyze most peptide bonds within a protein molecule. Therefore, its use on substrates like legume proteins causes a high degree of hydrolysis, producing many peptides of small sizes [ 43 ]. The low DH values obtained in fava bean and chickpea LPH with alcalase could be related to vicilin, as this protein is known for its emulsifying, foaming and gelling properties [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The commercial enzyme used for the hydrolysis showed to be very efficient compared to the enzymes used by Kong et al (2008) with only 18.36 DH % in 180 min. Ahmadifard et al (2016) used the commercial enzyme Alcalase to hydrolyze soy protein, obtaining 12.50 DH % after 60 min, whereas Corolase 7089 reached 47.91 DH % at 60 min. A reasonably low concentration of enzyme was needed to obtain hydrolysates.…”
Section: Discussionmentioning
confidence: 99%